2022
DOI: 10.1039/d2ta04246k
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven efficient dry reforming of methane over Pt/La2O3 with long-term durability

Abstract: The instability caused by coking and catalyst sintering during dry reforming of methane (DRM) is a major obstacle to their commercialization. Herein, Pt/La2O3 exhibits high yield of syngas and satisfactory...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Thus, the thermocatalytically active center of Pt and the photocatalytically active center of TiO 2 together enhance the DRM process. Gao et al [131] utilized photocatalytic/photothermal catalytic coupling for light-driven and efficient DRM reactions and designed a Pt/La 2 O 3 catalyst capable of absorbing full-wavelength sunlight. Under light irradiation, the local surface plasmon resonance on Pt/La 2 O 3 excites more hot electrons and oxygen vacancies and triggers an increase in the surface temperature of the catalyst, promoting the dissociative conversion of CH 4 to CHx and H + , which are further converted to C* and H 2 .…”
Section: Photothermal Catalysismentioning
confidence: 99%
“…Thus, the thermocatalytically active center of Pt and the photocatalytically active center of TiO 2 together enhance the DRM process. Gao et al [131] utilized photocatalytic/photothermal catalytic coupling for light-driven and efficient DRM reactions and designed a Pt/La 2 O 3 catalyst capable of absorbing full-wavelength sunlight. Under light irradiation, the local surface plasmon resonance on Pt/La 2 O 3 excites more hot electrons and oxygen vacancies and triggers an increase in the surface temperature of the catalyst, promoting the dissociative conversion of CH 4 to CHx and H + , which are further converted to C* and H 2 .…”
Section: Photothermal Catalysismentioning
confidence: 99%
“…Another is the lack of durable catalysts due to catalyst deactivation by severe coking, [14,15] which originates from thermodynamically inevitable side-reactions of CH 4 pyrolysis and CO disproportionation. [12,13] Recently, an approach of light-driven catalytic (photothermocatalytic) CO 2 reduction with CH 4 , [2][3][4][5][6][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] H 2 O, [47][48][49][50][51][52] and H 2 [53][54][55][56][57][58][59][60][61] using inexhaustible solar energy has been developed. It is very promising as it well integrates the low energy consumption of photocatalysis with the high catalytic efficiency of thermocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the photothermocatalytic CO 2 reduction approach, photothermocatalytic DRM is very promising as high production rates of syngas and light-to-chemical energy conversion are simultaneously achieved. [2][3][4][5][6][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Intensive studies have identified metallic Ni-based catalysts as the most promising candidate for both conventional thermocatalytic and lightdriven catalytic DRM owing to their earth-abundance, inexpensiveness, and high initial activity comparable to precious metal catalysts. [9][10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Introductionmentioning
confidence: 99%
“…have been reported to possess better resistance to coking than non-precious group VIII metal catalysts, but coking is still inevitable. 21–27,42–44 Secondly, so far, high r and η have been achieved only with high solar light intensities (more than 192 kW m −2 ); 18–20,45–47 thus, an expensive solar concentrated system such as solar thermal power generation is necessary. In recent years, scientists have suppressed carbon buildup and improved catalytic activity by preparing multi-component alloy catalysts, catalysts with reactive oxygen species, and ion-doped catalysts; however, carbon buildup is still unavoidable and the light intensity used is high ( e.g.…”
Section: Introductionmentioning
confidence: 99%